Loss of slit protein nephrin is associated with reduced antioxidant superoxide dismutase expression in podocytes shed from women with preeclampsia. Issue 13 (6th July 2018) - Wang, Yuping; Zhao, Shuang; Gu, Yang; Lewis, David F.
Abstract: Recent findings of podocyte shedding/podocyturia highlight the central significance of podocyte injury in preeclampsia, a hypertensive disorder unique to human pregnancy. To test the hypothesis that oxidative stress contributes to kidney podocyte injury in preeclampsia, we specifically examined expression and distribution of antioxidant CuZn‐SOD with nephrin and podoplanin in shed podocytes from women with preeclampsia. Human podocyte AB 8/13 cells served as control. We found that CuZn‐SOD was localized at the front/outreach region of nephrin at the cell periphery (foot process areas) in control podocytes and expression of CuZn‐SOD, nephrin, and podoplanin were all dislocated or lost in shed podocytes from preeclamptic patients. We further tested oxidative stress‐induced nephrin shedding in podocytes, in which AB 8/13 podocytes were cultured under lowered oxygen condition (2%O2 ) or treated with hypoxic mimicking agent cobalt chloride. Our results showed that reduced nephrin and podoplanin expression were associated with downregulation of CuZn‐SOD expression in podocytes when cells were cultured under lowered oxygen or hypoxic conditions. Nephrin shed in urinary specimen from preeclamptic women was also determined by immunoprecipitation/immunoblotting. The molecular sizes of nephrin that corresponded to that were lost when cells were cultured under hypoxic conditions. We concluded that increased oxidative stress plays a significant role in inducing podocyte protein shedding in preeclampsia. Abstract : In this study, we found that reduced nephrin and podoplanin expression is associated with loss of CuZn‐SOD expression in shed podocytes from preeclamptic patients. We further found that increased oxidative stress could induce podocyte nephrin shedding and cellular dislocation, which corresponds to shed nephrin detected in the patient urine specimen. Thus, our results provide plausible evidence that increased oxidative stress is a contributing factor of podocyte injury and podocyte protein shedding in preeclampsia.